Varenicline – a new pharmacotherapy for smoking cessation in primary care practice - Robson, Noorzurani (AOSIS, 2010)
Background: Cigarette smoking causes significant morbidity and mortality and is a major public health concern worldwide. Primary care doctors are in a unique position that enables them to promote smoking cessation, as smokers are more aware of their health at the time of their clinic visit. It is thus important to offer effective treatment to help smokers stop smoking. Methods: A search of PubMed was done up to 16 December 2009, using the keywords “varenicline” alone, “varenicline” and “family medicine”, and “varenicline” and “primary care”. The search produced 426 articles on varenicline. The articles that were chosen were case reports, meta-analyses, review articles and clinical trials published in English. Results: A new drug called varenicline has recently been introduced to assist smoking cessation. It is an α4β2 nicotinic acetylcholine receptor partial agonist. Varenicline has a unique action that relieves the cravings and withdrawal symptoms that occur during smoking abstinence, while blocking the receptor and preventing any reward from additional smoking. It has been shown to be efficacious for smoking cessation in normal smokers; however, its safety in smokers with mental health problems needs to be elucidated. Conclusion: The currently available data support the effectiveness of varenicline to treat nicotine dependence, but caution is needed in smokers with mental health problems. Thus, primary care doctors have a new pharmacological option to offer smokers who wish to stop smoking.